2015
DOI: 10.1002/cncr.29596
|View full text |Cite
|
Sign up to set email alerts
|

Association between medical home enrollment and health care utilization and costs among breast cancer patients in a state Medicaid program

Abstract: Background The patient centered medical home (PCMH) is increasingly being implemented in an effort to improve and coordinate primary care, but its effect on health care utilization among breast cancer patients remains unclear. The objective of this study was to examine health care utilization and expenditures as a function of PCMH enrollment among breast cancer patients in North Carolina's Medicaid program. Methods North Carolina Medicaid claims linked to North Carolina Central Cancer Registry records (2003-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 25 publications
0
34
1
Order By: Relevance
“…Of the 23 articles included, 12 (52%) were published in the peer‐reviewed literature, and 13 (57%) published results and thus could be assessed for quality. Table summarizes the quality of evidence assessments conducted on the 13 studies that reported outcomes . Over one‐half (n = 7; 54%) received a weak global rating, and the remaining studies (n = 6; 46%) received a moderate global rating.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 23 articles included, 12 (52%) were published in the peer‐reviewed literature, and 13 (57%) published results and thus could be assessed for quality. Table summarizes the quality of evidence assessments conducted on the 13 studies that reported outcomes . Over one‐half (n = 7; 54%) received a weak global rating, and the remaining studies (n = 6; 46%) received a moderate global rating.…”
Section: Resultsmentioning
confidence: 99%
“…Two analyses of the impact of primary care‐focused PCMHs on cancer care reported that 1 reduced value, whereas the other was value‐neutral . Specifically, an analysis of utilization and costs associated with patients who had breast cancer in the North Carolina Medicaid PCMH indicated reduced value through increased monthly outpatient service utilization, no effect on ER visits or hospitalizations, and a $429 per month increase in expenditure for the first 15 months . Notably, this increase in cost was no longer significant at 24 to 36 months postdiagnosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, according to another study, the impact of PCMH enrollment was, in some measure, associated with increased resource use and cost. A significant increase in monthly Medicaid expenditures and the number of outpatient visits for PCMH enrollees was observed over the first 15 months from diagnosis compared to non-PCMH participants (p<0.001), with no significant impact on inpatient hospitalizations or ED visits [33]. ■ ACO vs. non-ACO (FFS).…”
Section: Implicit Payment Reforms Targeting Delivery Of Carementioning
confidence: 98%